Measuring quality of gout management in residential aged care facilities. Issue 3 (28th November 2022) - Nguyen, Amy D; Lind, Kimberly E; Day, Richard O; Ross, Daniel; Raban, Magdalena Z; Georgiou, Andrew; Westbrook, Johanna I
Abstract: Objective: Gout, a common form of arthritis, can be controlled successfully with pharmacotherapy and is thus an ideal model for examining chronic disease management. Our aim was to examine treatment of gout evaluated in accordance with general management guidelines for gout as applied to Australian residential aged care facilities. Methods: Electronic health record data linked with aged care clinical notes and electronic medication administration information (11 548 residents in 68 residential aged care facilities, >65 years of age) were interrogated to identify people with gout, other chronic conditions and gout medication use. The outcomes examined were the proportion receiving urate-lowering therapy (ULT; preventative medication) and/or colchicine/non-steroidal anti-inflammatory drug (NSAID) (to treat gout flares), the number of ULT and colchicine/NSAID treatment episodes (periods of continuous days of medication use) and the duration of these treatment episodes. Results: The cohort included 1179 residents with gout, of whom 62% used a ULT, with a median of one episode of use for a very short duration [median = 4 days, median of use in total (i.e. repeated use) = 52 days]. Among residents with gout, 9% also used colchicine or an NSAID. Female residents were less likely to receive ULT and for shorter periods. Conclusion: Nearly one-third of residents with gout did not receive ULT. In those receiving ULT, recurrent short courses were common. Overall, management of gout in aged care residents appears to be suboptimal, largely owing to intermittent and short exposure to ULT, and with female residents at greater risk of poor gout management. Lay Summary: What does this mean for patients? Residents living in aged care facilities are at risk of receiving suboptimal pharmacological management of their gout. Instead of receiving the recommended long-term urate-lowering therapies, aged care residents have intermittent short exposures to these medications, which might not elicit the appropriate protection against painful gout flares. Female aged care residents are at greater risk of receiving poor gout management. Further research to explore the reasons why gout management is not concordant with guidelines within the residential aged care setting is required. This will ensure that residents receive appropriate gout management to minimize the debilitating painful effects of gout. This study also demonstrates the ability to use routinely collected patient data to improve delivery of care in the aged care setting.